2013
DOI: 10.1177/0022002712464850
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Terrorism on Investment Decisions of Farmers

Abstract: This article provides evidence for a particular channel through which sustained terrorism in rural areas may affect growth in developing countries. Using micro-level data from agricultural surveys during the period of insurgency in Punjab (India), I find significant negative effects of terrorism on the level of investment in long-term agricultural technology, but effects are small and insignificant for short-term investment. The presence of a major terrorist incident in a district in a year reduces long-term f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…Also, households often cope with conflict by reorganizing their livelihoods in ways that reduce their risk from harm at the cost of lower income. Farmers respond to insecurity and the uncertainty of property rights during conflict by pre-emptively selling livestock, switching to 'robust crops' that require few visits to the fields and by reducing long-term productivity enhancing investments such as wells (Singh 2013 andVerpoorten 2009). These are all examples of how the shortening of time-horizons, discussed in Section 2, leads to major distortions in the economic activities that sustain the poor and the vulnerable.…”
Section: Health Education and Livelihoodsmentioning
confidence: 99%
“…Also, households often cope with conflict by reorganizing their livelihoods in ways that reduce their risk from harm at the cost of lower income. Farmers respond to insecurity and the uncertainty of property rights during conflict by pre-emptively selling livestock, switching to 'robust crops' that require few visits to the fields and by reducing long-term productivity enhancing investments such as wells (Singh 2013 andVerpoorten 2009). These are all examples of how the shortening of time-horizons, discussed in Section 2, leads to major distortions in the economic activities that sustain the poor and the vulnerable.…”
Section: Health Education and Livelihoodsmentioning
confidence: 99%
“…Relying on investment data from 510 Indian farmers in 46 sub-districts during July 1978 to June 1990, Singh (2013 found that terrorism was negatively associated with the level of investment in the long term. However, these effects were small and statistically insignificant during the short term.…”
Section: Theoretical Framework For Foreign Direct Investmentsmentioning
confidence: 99%
“…A growing body of economic research estimates the negative economic impacts of conflict, where conflict is proxied by measures of violence. These papers find that conflict leads to the destruction of assets, deterioration of human capital, weakening of institutions, and changes in economic behaviour, all of which result in lower income and consumption levels (Akresh et al 2011;Blattman and Miguel 2010;Camacho 2008;Grosjean 2014;Justino 2011;Justino and Verwimp 2013;León 2012;Rockmore 2016;Serneels and Verpoorten 2015;Singh 2012;Verpoorten 2009). Recent papers have found unexpected positive impacts of being exposed to violence and being forcibly recruited on political participation, collective action, and pro-social behaviour, yet these effects vary depending on the dynamics of conflict and violence against civilians (Arjona et al 2017;Bauer et al 2016;Bellows and Miguel 2009;Blattman 2009;Cassar et al 2013;Gilligan et al 2014;Voors et al 2012).…”
Section: Introductionmentioning
confidence: 99%